The creative imagination indeterminacy and embodiment in the writings of Kant, Fichte, and Castoriadis - Heap, Jodie Lee (Social imaginaries., 2021)
"By offering an original elucidation of the notion of the imagination in the writings of Immanuel Kant, Johann Fichte, and Cornelius Castoriadis, this book addresses and brings to the fore the significance of the imagination as the ontological source of human creation"--